PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI GRAND IXORA KUTA RESORT - I Made Arie Kasnawa; Ni Ketut Dewi Irwanti; Sulistyoadi Jokosaharjo (Journal of Tourism and Interdiciplinary Studies, 2021)
This study aims to determine the effect of communication (X1) and work discipline (X2) partially or simultaneously on employee performance (Y) at Grand Ixora Kuta Resort. The respondents used in this study were all employees of Grand Ixora Kuta Resort with a total of 86 respondents. The data used in this study are primary data originating from questionnaires, then the questionnaires were tested using validity and reliability tests followed by classic assumption tests and hypotheses proved using multiple linear regression analysis. The results showed that communication (X1) and work discipline (X2) had a partial effect on employee performance (Y) at Grand Ixora Kuta Resort, this is indicated by the value of the calculated communication variable t (X1) of 3.254> t table which is 1.989 with a value significance of 0.002 <0.05 and the value of t counts the work discipline variable (X2) of 4.406> t table which is 1.989 with a significance value of 0.000 <0.05. F count value of 37,629 is greater than F table of 2,716 (df1 = 3, df2 = 82) so that it can be concluded that simultaneous communication variables (X1) and work discipline (X2) affect employee performance (Y) at Grand Ixora Kuta Resort . The coefficient of determination shows the value of R Square of 0.476. This shows that 47.6% of employee performance (Y) in Grand Ixora Kuta Resort is influenced by communication (X1), and work discipline (X2), while the remaining 52.4% is influenced by other variables outside of this study.